2004
DOI: 10.1021/ja046151+
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in One-Dimensional Vanadium−Benzene Sandwich Clusters

Abstract: A molecular beam of multilayer vanadium-benzene organometallic complexes Vn(C6H6)m was produced by a laser vaporization synthesis method. The magnetic moments of the complexes were measured by a molecular beam magnetic deflection technique, and were found to increase with the number of vanadium atoms in the cluster, showing that the unpaired electrons, which occupy the nonbonding dsigma orbitals localized on the metal atoms, couple ferromagnetically. These sandwich species represent a new class of one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
201
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(217 citation statements)
references
References 31 publications
16
201
0
Order By: Relevance
“…This prediction is particularly exciting because V is not ferromagnetic in the bulk. Recent magnetic deflection experiments have verified this prediction (146).…”
Section: Clusters In Chemistrymentioning
confidence: 74%
“…This prediction is particularly exciting because V is not ferromagnetic in the bulk. Recent magnetic deflection experiments have verified this prediction (146).…”
Section: Clusters In Chemistrymentioning
confidence: 74%
“…Molecular magnets with a tendency towards one-dimensionalization are synthesized and experimentally observed as quasi-1D structures showing intriguing magnetic and structural properties. 18,19 In order to understand the structure-property relation in these new materials on the basis of the electronic structure, ab initio calculations based on the density functional theory play an important role. The low-dimensionality, the chemical complexity, the open structure, and the large variety of chemical elements in these systems ask for flexible ab initio methods, which can cope with these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Another difficulty with CNT is that the devices are unlikely to be very reproducible due to the wide assortment of tube size and helicity that is produced during synthesis. Wide variation in device behavior was reported in the CNT experiment [4].Recently, an experimental study suggested that the unpaired electrons on the metal atoms couple ferromagnetically in the multidecker organometallic sandwich Vbenzene (Bz) complexes, i.e., V n (Bz) n+1 clusters [7]. The FM sandwich clusters are supposed to serve as nanomagnetic building blocks in applications such as recording media or spintronic devices.…”
mentioning
confidence: 99%
“…Recently, an experimental study suggested that the unpaired electrons on the metal atoms couple ferromagnetically in the multidecker organometallic sandwich Vbenzene (Bz) complexes, i.e., V n (Bz) n+1 clusters [7]. The FM sandwich clusters are supposed to serve as nanomagnetic building blocks in applications such as recording media or spintronic devices.…”
mentioning
confidence: 99%